Strengthening Creative Local Human Resources In The Field Of Business Models And Marketing Of Coffee Ecotourism In Sukodono Village, Malang District - Satria, Dias; Hascaryani, Tyas Danarti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Sukodono Village in Malang Regency has rich resource potential, but faces branding and optimization challenges. The level of community literacy related to science and technology is still low, affecting the development of a sustainable coffee ecotourism business model. Assistance in community empowerment in Sukodono Village, by developing a coffee ecotourism business model through a business model canvas (BMC), can be a solution to this problem. Coffee ecotourism development begins with a branding process through existing promotional media, including village maps, websites, and taglines to increase the popularity of Sukodono Village as a coffee ecotourism destination. Improving the quality of creative local human resources must also be encouraged so that they can apply modern business models in an effort to increase the competitiveness of the area.